1998
DOI: 10.1021/ja972574i
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Substrate Identity in Determining Monolayer Motional Relaxation Dynamics

Abstract: We report on the lifetime and motional dynamics of Zirconium Phosphonate (ZP) monolayers containing oligothiophene chromophores in a range of concentrations. Monolayers were formed on fused silica substrates and on a 15 Å oxide layer formed on crystalline Si(100) substrates. For both interfaces, the fluorescence lifetime behavior of the chromophores is identical and does not depend on chromophore concentration within the monolayer. Transient anisotropy measurements reveal that, for both substrates, the chromop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Excitation and emission slits were adjusted according to spectral intensity. Our previous reports on the linear response of oligothiophene monolayers have shown that their steady-state spectra are very similar to solution phase spectra, , and this similarity is demonstrated in Figure a,b for BDP.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Excitation and emission slits were adjusted according to spectral intensity. Our previous reports on the linear response of oligothiophene monolayers have shown that their steady-state spectra are very similar to solution phase spectra, , and this similarity is demonstrated in Figure a,b for BDP.…”
Section: Methodssupporting
confidence: 69%
“…For example, deposition of BDP and 1,6-hexanediylbis(phosphonic acid) (HBPA) from ethanol produces a monolayer where BDP is adsorbed preferentially to the surface . Conversely, the deposition of QDP from a solution of 80% DMSO, 18% EtOH, and 2% H 2 O yields a monolayer where the composition is related directly to the solution composition . We find that this solvent system works equally well for both QDP and BDP.…”
Section: Methodsmentioning
confidence: 85%
“…Self-assembled monolayers (SAMs) have received a great deal of attention for their fascinating potential technical applications such as nonlinear optics and device patterning (Horne & Blanchard, 1998;Morhard et al, 1997;Bierbaum et al, 1995). They also have been used as an ideal model to investigate the effects of intermolecular interactions in the molecular assembly systems (Schertel et al, 1995;Yan et al, 2000;Himmel et al, 1997;Jung et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…LB films are formed on a trough where surface pressure can be controlled, and the morphology of the interface can be imaged using Brewster angle microscopy (BAM). The deposition of the films on a solid support is well established, and the means by which the monolayer interacts with the support is based on the chemical identity of the support surface. For example, a silica surface possessing terminal silanol functionalities will interact differently with a monolayer film than if the surface was terminated with phosphonate or carboxylate functionalities. The functionalization of the support surface also allows for the use of metal ions to mediate support–monolayer interactions, and there is ample literature precedent for this structural motif. ,, Metal ions including Ca 2+ , Cd 2+ , Ba 2+ , Mn 2+ , Zn 2+ , and Tb 3+ dissolved in the aqueous subphase of an LB trough interact with the hydrophilic headgroups of fatty acids (e.g., arachidic and stearic acids), and the complex can be deposited as a mono- or multilayer on a solid support by vertical dipping. Metal ions provide a means to control the organization of monolayer films, which can mediate organization, fluidity, and stability.…”
Section: Introductionmentioning
confidence: 99%